Assessment of image quality of cervical spine complications using Three Magnetic Resonance Imaging Sequences - Nabaa A. Rasheed Naji (مجلة بغداد للعلوم)
Examining and comparing the image quality of degenerative cervical spine diseases through the application of three MRI sequences; the Two-Dimension T2 Weighed Turbo Spin Echo (2D T2W TSE), the Three-Dimension T2 Weighted Turbo Spin Echo (3D T2W TSE), and the T2 Turbo Field Echo (T2_TFE). Thirty-three patients who were diagnosed as having degenerative cervical spine diseases were involved in this study. Their age range was 40-60 years old. The images were produced via a 1.5 Tesla MRI device using (2D T2W TSE, 3D T2W TSE, and T2_TFE) sequences in the sagittal plane. The image quality was examined by objective and subjective assessments. The MRI image characteristics of the cervical spines (C4-C5, C5-C6, C6-C7) showed significant differences among the three sequences used P˂0.05 with the exception of the contrast P˃ 0.05. For the cervical spines (C4-C5), the minimum CNR was noticed with the T2_TFE sequence. For the cervical spines (C5-C6), the CNR and SNR were higher when they were assessed by the 2D T2W TSE sequence as compared to the other sequences. The same findings were observed with the cervical spines (C6-C7). The subjective assessment of the degenerative cervical spine diseases showed that the T2_TFE sequence is excellent in terms of viewing the central stenosis and foraminal stenosis. The best MRI diagnostic imaging can be obtained using the Turbo Field Echo (T2_TFE) and the Three-Dimension T2 Weighted Turbo Spin Echo (3D T2W TSE) sequences to gain detailed diagnostic information regarding the central stenosis and foraminal stenosis of the cervical spines (C4-C5, C5-C6, C6-C7)